Professional knowledge among Swedish and Saudi healthcare practitioners regarding oro‐facial pain in children and adolescents. (2nd July 2015) - Al‐Khotani, A.; Naimi‐Akbar, A.; Björnsson, O.; Christidis, N.; Alstergren, P.
Summary: Oro‐facial pain (OFP) and temporomandibular disorders (TMD) in children and adolescents are a growing problem. To meet patients' healthcare needs, professionals must perform their work intuitively and with quality. Therefore, a high degree of professional knowledge is necessary. To investigate the professional knowledge regarding OFP/TMD in children and adolescents among Swedish and Saudi Arabian dental and medical specialists compared with Swedish OFP specialists. One questionnaire including the four domains Chronic pain and behaviour; Aetiology; Diagnosis and classification; Treatment and prognosis was distributed to 383 potential participants, that is physicians and dentists in Sweden and Saudi Arabia. The Swedish OFP/TMD specialists were used as a reference group. The response rates from Sweden and Saudi Arabia were 49% and 86%, respectively. The degree of agreement was highest in the domain Chronic pain and behaviour, especially for the Swedish groups. Regarding the other three domains, the agreement was modest to poor. In general, Swedish groups showed a higher agreement with Swedish OFP/TMD specialists than Saudi Arabian groups. This study shows that professional knowledge regarding OFP/TMD in children and adolescents is limited among Swedish and Saudi Arabian dental and medical professionals compared to Swedish OFP/TMD specialists. In Swedish groups, the professional knowledge is more accurate than in the corresponding Saudi Arabian. With these results in mind, and the frequent prevalence of OFP/TMD in children and adolescents, one can draw the conclusion that there is a need for modern medical education regarding OFP/TMD among both physicians and dentists, especially in Saudi Arabia.